VIA /VILI Guided Cervical Punch Biopsy for Detection of CIN and Early Invasive Cervical Cancer in Low Resource Setting - Meena, Naik; Rekha, Ratnani; Anju, Pungle (International Journal of Innovative Research in Medical Science, 2017)
Aim of Study - Evaluation of VIA/VILI guided cervical biopsy for diagnosis of cervical pre invasive and early invasive lesions of cervix for resource poor settings. Introduction and background - India has one fifth of burden of cervical cancer. In absence of an organized screening program most women present in advanced stages of cancer which is beyond surgical treatment. Due to lack of resources and trained personel for Pap based screening and colposcopy many patients remain undiagnosesd and untreated. VIA based screening have been extensively studied and have been found to be highly sensitive, cost effective and simple procedure for screening of patients in low resource settings. However after screening the need for colposcopy and LEEP leaves this patients untreated due to lack of facilities and trained personel in remote areas for colposcopy and LEEP .hence we studied VIA /VILI guided biopsy without using colposcopy as a method of diagnosis of cervical preinvasive lesions. Material and Methods - This study was conducted in CCM medical college hospital, kachandur, a tertiary medical college hospital in Durg district of Chhatisgarh. This hospital caters to the rural population of remote areas of Chhattisgarh community camps are organised three times a week in remote areas. All female patients coming to gynae OPD with any complaint are screened with VIA+VILI. All patients with Positive VIA/VILI were subjected fro VIA/VILI guided biopsy under local an aesthesia histopathological reports reviewed and correlated, and compared with the final histopathology report for those who underwent hysterectomy for various reasons, to calculate sensitivity, specificity, positive and negative predictive value or VIA /VILI guided biopsy for detection of CIN and early invasive cervical lesions. Conclusion - VIA /VILI guided cervical biopsy is a good alternative for very low resourse setting where both infrastructure and trained personnel for colposcopy and LEEP are lacking. As lack of these resourses and personel in periphery forces the women to travel long distances for a diagnostic test. Or they are left undiagnosed if they cannot travel to centres equipped with these facilities.